Dietary Plasticity of African Clawless Otters (Aonyx capensis): An Assessment of Seasonal Variation in Prey Availability - Marli Burger; Andre Ganswindt; Tshepiso L. Majelantle; Juan Scheun; Andrea B. Webster (Ecology and Evolution, 2025)
ABSTRACT African clawless otters (Aonyx capensis) are opportunistic feeders with a broad dietary niche. Variation in their diet can be influenced by environmental and anthropogenic factors, which can affect seasonal and longitudinal prey availability. Flexibility in the diet allows African clawless otters to adapt to these changes and exploit novel prey items when available. Seasonal examination of otter spraints from three different locations across South Africa demonstrates that African clawless otters are able to shift from their preferred crab‐based diet to a fish‐ or insect‐based diet in response to environmental and anthropogenic drivers. Here we provide direct evidence of African clawless otters in terrestrial environments shifting to an insect‐dominated diet when this resource is available. The dietary plasticity and response of this species to the shifts in available prey items may be an important factor for future consideration in conservation management of the species.